Proteomic and metabolomic analysis of Litopenaeus vannamei infected with infectious hypodermal and hematopoietic necrosis virus (IHHNV) - Fan Yang; Shou-Xin Luo; Zhi-Peng Yin; Ling-Jun Si; Ting Li; Lin-Rui Chang; Dong-Chun Yan (Aquaculture, 2027)

Thermodynamically favored fluorine refilling stabilizes oxygen vacancies for ultrafast and wide-temperature aqueous zinc-ion batteries - Daming Chen; Yang Ming; Jimin Fu; Chuanwei Zhi; Zijian Li; Wei Cai; Hanbai Wu; Xin Hu; Rujun Yu; Shou Shi; Jing Liu; De-Yi Wang; et al. (Chemical Engineering Journal, 2026)

Avermectin induces developmental toxicity and immunotoxicity in zebrafish larvae - Wei-Guo Wang; Shou-Lin Li; Da-Wei Yan; Yun-Fei Sha; Wen-Ping Xu; Jia-Gao Cheng; Zhong Li; Li-Ming Tao; Yang Zhang (Journal of Environmental Sciences, 2026)

Revealing the dominant role of pectin in softening texture and enhancing drying behaviors of grapes after cold plasma pretreatment - An-An Zhang; Fan Yang; Ming-Qiang Xu; Wei-Peng Zhang; Jin-Run Li; Hai-Bin Yang; Jing-Shou Zhang; Wei-Qiao Lv; Hong-Wei Xiao (Food Research International, 2026)

Research on Multi-Scale Feature Extraction and Mineral Content Inversion in Elemental Logging Based on an Integrated RF-CNN-XGBoost Model - You-hai Sun; Zhong-jian Li; Yong-qiang Zhao; Ze-bin Gong; Yang Zhang; Shou-qing Zhang; Dan Yu (Applied Geophysics, 2026)

Eccentric coaxial wet-spun magnetic composite actuators with decoupled magneto-pneumatic shape-morphing for biomedical applications - Ping-an Yang; Yixuan Han; Chunyan Mo; Mengjie Shou; Rui Li; Yi Lu; Decheng Wu; Qiao Chen; Zhiwei Huang (Chemical Engineering Journal, 2026)

Population Decline, Inbreeding and Hybridization Shape the Genetic Vulnerability of a Critically Endangered Seabird - Guoling Chen; Chenqing Zheng; Lanhui Peng; Hongzhou Lin; Feng Dong; Shou‐Hsien Li; Yiwei Lu; Siyu Wang; Zhongyong Fan; Yinan Fu; Peng Ding; Jian Zhang; et al. (Molecular Ecology, 2026)
Many endangered species have been rescued from the brink of extinction, yet their long‐term viability remains uncertain due to the prolonged genetic consequences of severe bottlenecks. In particular, the combined effects of inbreeding and hybridization with closely related species remain poorly understood. Using a comparative conservation genomic framework, we investigated these issues in the Chinese crested tern ( Thalasseus bernsteini ), a critically endangered seabird once presumed extinct but which has increased to approximately 100 individuals over the past two decades and its close relative, the great crested tern ( T. bergii ). We demonstrate that the Chinese crested tern has experienced ongoing genetic erosion. Its prolonged population decline has intensified genetic drift and reduced the efficiency of purifying selection, resulting in genome‐wide accumulation of highly deleterious mutations. Highly inbred individuals also carry significantly more homozygous deleterious mutations than less inbred individuals. In both species, runs of homozygosity (ROH) show a relative enrichment of moderately and weakly deleterious mutations. Even more concerning, we found an enrichment of moderately and weakly deleterious mutations in putatively introgressed regions in both species, suggesting that occasional hybridization may have facilitated the spread of deleterious variants and could potentially compromise long‐term fitness. These findings highlight that severe bottlenecks have lasting genomic consequences and that both inbreeding and hybridization can increase the genetic vulnerability of small populations—underscoring the importance of management strategies that promote population growth and sustained genetic monitoring.

Corrigendum to Avermectin induces developmental toxicity and immunotoxicity in zebrafish larvae. Journal of Environmental Sciences (2026), doi: https://doi.org/10.1016/j.jes.2026.03.02 - Wei-Guo Wang; Shou-Lin Li; Da-Wei Yan; Yun-Fei Sha; Wen-Ping Xu; Jia-Gao Cheng; Zhong Li; Li-Ming Tao; Yang Zhang (Journal of Environmental Sciences, 2026)

Corrigendum to “Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis citrina Baroni)” [Food Chem. 506 (2026) 148147] - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Fulvic acid-mediated oxidative stress and neurotoxicity in earthworms exposed to agricultural film-derived polyethylene microplastics: multifactorial regulation and biomarker dynamics - Yuicui NING; Zhipeng CHEN; Shou WANG; Yazhou YANG; Zihan XU; Hanyue CAO; Shoujun YANG; Bohang LI; Dongxing ZHOU (Pedosphere, 2026)

Grass mulching optimizes microbial communities and enhances carbon nitrogen cycling in peach orchard soils across slope positions - Chengyi Huang; Caiyun Lu; Huijuan Huang; Hongbin Zhang; Liu Yang; Yian Chen; Lijin Lin; Kairui Zhang; Wenjie Liu; Dan Zhu; Hongping Li; Shou Yan (Nutrient Cycling in Agroecosystems, 2026)

The Strawberry C2H2 Zinc Finger Protein FvZFP57 Positively Regulates Drought Stress - Shou-bing Chen; Zhi-kai Song; Jian Guo; Ming-di Yang; Shuai-jie Li; Ming-li Zhu; Junxiang Yu; Meng Xu; Yi-hua Liu (Journal of Plant Growth Regulation, 2026)

Diapause termination alters the m6A methylation profiles and regulates gene expression associated with early embryonic development in the silkworm (Bombyx mori) - Zhi-Hao Huang; Jia-Yue Yang; Cai-Ping Hou; Shi-Huo Liu; Bing Li; Jie Wang; Shou-jun Huang; Jia-Ping Xu (Journal of Insect Physiology, 2026)

Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis lilioasphodelus L.) - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Influence of endometritis and LPS stimulation on the expression of bta-miR-200b and PI3K/AKT and NF-κB pathways in in vivo or cultured bovine endometrial epithelial cells - Yajing Chen; Lifang Mi; Shou Li; Khao Keonam; Jing Yang; Kangfeng Jiang; Xiaobing Li (Theriogenology, 2025)

Revolutionizing toxicological risk assessment: integrative advances in new approach methodologies (NAMs) and precision toxicology - Qiu-Shuang Sheng; Bin Liu; Xiao Wang; Lei Hua; Shou-Cheng Zhao; Xiao-Zhong Sun; Mu-Yang Li; Xiang-Yu Zhang; Jia-Xu Wang; Pei-Li Hu (Archives of Toxicology, 2025)

Theaflavin 3,3′-digallate suppresses metastasis and reduces insulin-like growth factor-1-induced cancer stemness and invasiveness in human melanoma cells - Ju-Pi Li; Yi-Hsien Hsieh; Yi-Hsun Lee; Wen-Yi Tsai; Shun-Fa Yang; Yih-Shou Hsieh; Pei-Ni Chen (Chemico-Biological Interactions, 2025)

Copper pyrithione exposure-induced copper accumulation compromises mouse oocyte maturation - Sheng-Ji Yang; Ming Liu; Yin-Qing Li; Yong-Sheng Wang; Ze-Qun Duan; Jing-Jing Wang; Hai-Miao Lv; Shou-Xin Zhang; Li-Jun Huo (Journal of Environmental Management, 2025)

Reversal of neurodevelopmental toxicity induced by combined exposure to the neonicotinoid insecticides acetamiprid and imidacloprid in zebrafish through targeting DRP-1: insights into mitophagy and apoptosis mechanisms - Yuzhi Zhao; Shaozhuo Wang; Siyue Tan; Gaoyuan Wang; Haojie Zhou; Chengyu Geng; Chunjin Li; Yuewen He; Yifan Shi; Zhongxiu Deng; Siyu Chen; Qitong Yuan; et al. (Environmental Pollution, 2025)

Editorial Expression of Concern: HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Olfactory dysfunction induced by pesticides: Adverse outcomes, emerging mechanisms, and risk for neurodegenerative diseases - Lin Wang; Si-Yang Liu; Han-Yue Zheng; Shou-Min Fang; Li Zhuo; Feng Xu; Quan-You Yu (Pesticide Biochemistry and Physiology, 2025)

Phosphorous availability and plant growth regulated by Fe(III)-reducing microbial communities in paddy soil - Danyang Shou; Weijie Nie; Lijun Lin; Guiqin Yang; Dongkun Ouyang; Li Zhuang (Journal of Soils and Sediments, 2025)

Targeted discovery of oxygen-bridged sesquiterpenes from Cinnamomum migao by MS/MS-based molecular networking and their neuroprotective activities - Lang Zhou; Xiong Pan; Fa-ju Chen; Mei Peng; Yu Wang; Ming Gao; Li-shou Yang; Liang-qun Li; Juan Yang; Xiao-sheng Yang; Qi-ji Li (Phytochemistry, 2025)

Upregulation of circRNA_0002286 protects against brain ischemia/reperfusion injury after remote ischemic postconditioning via microRNA-124-3p/VLCAD axis - Chun-Yan Li; Wei Ma; Jin-Wei Yang; Wei Liu; Kuang-Pin Liu; Xiao-Hua Weng; Shou-Rui Niu; Shen Li; Jian-Hui Guo; Li-Yan Li (Journal of Molecular Histology, 2025)

Biomineralization mechanisms in the estuarine oyster (Crassostrea ariakensis): Unveiling the adaptive potential of mollusks in response to rapid climate change - Shen-Tong Wang; Li Li; Qi Yang; Wei Wang; Lu-Ping Wang; Shou-Du Zhang; Guo-Fan Zhang (Environmental Pollution, 2025)

Quantum circuit mapping based on discrete particle swarm optimization and deep reinforcement learning - Yang-Zhi Li; Wen Liu; Guo-Sheng Xu; Mao-Duo Li; Kai Chen; Shou-Li He (Swarm and Evolutionary Computation, 2025)

Crystal facet effect of the support in Ni/La2O2CO3 catalysts for toluene steam reforming - Shou-Yong Jiang; Yang Du; Yun-Jie Li; Zhi-Bin Wang; Hong-Xia Fan; Shou-Dong Xu; Zhen-Yi Du; M.D. Isobaev; Wen-Ying Li (Fuel, 2025)

New insights into microbial degradation of polyethylene microplastic and potential polyethylene-degrading bacteria in sediments of the Pearl River Estuary, South China - Guiqin Yang; Xiaoyun Quan; Danyang Shou; Xin Guo; Dongkun Ouyang; Li Zhuang (Journal of Hazardous Materials, 2025)

Enhancing the hydrophobicity of triboelectric sensors with biomimetic structure for motion recognition of field robots - Ruixue Sun; Pengfan Wu; Pei Li; Pingan Yang; Endian Cui; Mengjie Shou; Fayang Wang; Changrong Liao; Xiaojing Mu (Chemical Engineering Journal, 2025)

Enhanced synergistic effect of acidity and active phase for Ni-Co@NHZ-5-AT on hydroconversion of benzyoxybenzene to polycyclic alkanes - Xiao-Wei Yu; Yan-Jun Li; Yu-Hong Kang; Juan Gao; Pei-Lin Yang; Guang-Hui Liu; Shou-Long Gong; Xiao-Yu Kang; Yong Gao; Xian-Yong Wei; Wei Lu (Biomass and Bioenergy, 2025)

The Role of the Intestinal Flora and Its Derivatives in Neurocognitive Disorders: A Narrative Review from Surgical Perspective - Jian Huang; Tian-Shou Qin; Yun Bo; Yu-Jin Li; Rong-Sheng Liu; Yang Yu; Xiao-Dong Li; Jin-Can He; Ai-Xin Ma; Da-Peng Tao; Wen-Jun Ren; Jun Peng (Molecular Neurobiology, 2025)
Perioperative neurocognitive dysfunction is a significant concern for population health, impacting postoperative recovery and increasing the financial burden on patients. With an increasing number of surgical procedures being performed, the prevention and management of perioperative neurocognitive dysfunction have garnered significant attention. While factors such as age, lifestyle, genetics, and education are known to influence the development of cognitive dysfunction, recent research has highlighted the role of the gut microbiota in neurological health. An increased abundance of pro-inflammatory gut microbiota can trigger and worsen neuroinflammation, neuronal cell damage, and impaired cellular autophagy. Moreover, the inflammation-promoting gut microbiota can disrupt immune function, impair neuroautophagy, and affect the production and circulation of extracellular vesicles and neurotransmitters. These factors collectively play a role in the onset and advancement of cognitive impairment. This narrative review delves into the molecular mechanisms through which gut microbiota and their derivatives contribute to cognitive impairment, focusing on the impact of anesthesia surgery, changes in gut microbial populations, and perioperative cognitive impairment associations. The study suggests that alterations in the abundance of various bacterial species and their metabolites pre- and post-surgery may be linked to postoperative cognitive impairment. Furthermore, the potential of probiotics or prebiotics in addressing cognitive impairment is discussed, offering a promising avenue for investigating the treatment of perioperative neurocognitive disorders.

Microbiome changes and characteristics under nutrient injection for enhanced oil production at Daqing oilfield - Zi-Yue Fu; Wen-Tao Chen; Gui-Na Qi; Zhao-wei Hou; Yi-Fan Liu; Li-Bin Shou; Lei Zhou; Shi-Zhong Yang; Xiao-Lin Wu; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2025)

Towards wearable multifunctional cellulose nanofiber/silver nanowire/graphene oxide film: Electromagnetic protection, antibacterial, and motion monitoring - Zheng Wang; Shi-Bo Li; Xiao Yang; Hao Wang; Li-Jing Xie; Ze-Chao Tao; Qing-Qiang Kong; Shou-Chun Zhang; Hui Jia; Dong Jiang; Cheng-Meng Chen (Chemical Engineering Journal, 2024)

Experimental Study on Multistage Seismic Damage Process of Bedding Rock Slope: A Case Study of the Xinmo Landslide - Jing-Jing Tian; Tian-Tao Li; Xiang-Jun Pei; Jian Guo; Shou-Dao Wang; Hao Sun; Pei-Zhang Yang; Run-Qiu Huang (Journal of Earth Science, 2024)

Vibration reduction and efficiency enhancement effects of twisted rudders in submarines under small rudder angle conditions - Di Zhang; Jin-ming Ye; Wan-li Yang; Yuan-run Wu; Jian-lin Shou (Ocean Engineering, 2024)

Natural pyrethrins induce cytotoxicity in SH-SY5Y cells and neurotoxicity in zebrafish embryos (Danio rerio) - Wei-Guo Wang; Shou-Lin Li; Bin Liu; Ning Tang; Cheng Zhang; Xu-Feng Jiang; Li-Ming Tao; Wen-Ping Xu; Yang Zhang (Environmental Research, 2024)

Selective catalytic reduction of NOx with methane over cobalt-exchanged SSZ-39 zeolite - Jian Li; Lunjia Zhang; Ye Ma; Kai Fan; Juan Zhang; Jianping Wu; Wenfu Yan; Xiangju Meng; Qinming Wu; Fan Yang; Feng-Shou Xiao (Chemical Engineering Journal, 2024)

Electrocatalytic nitrogen reduction to ammonia at low overpotentials based on tungsten carbide doped by non-precious metal single cobalt atoms - Ya Gao; Meng-Jiao Zhu; Xian-He Liu; Guo-Liang Dai; Yi-Wen Zhou; Ze-Da Meng; Li Luo; Tian Gan; Feng Chen; Yu-Yang Zhou; Wen-Wen Deng; Shou-Qing Liu (Chemical Engineering Journal, 2024)

New alkaloids from Polygonatum zanlanscianense Pamp - Xue-Ke Zhang; Zhu-Zhen Han; Li Yang; Peng-Fei Zhang; Hong Zhang; Shou-Jin Liu (Natural Product Research, 2024)

Achieving high nitrogen and antibiotics removal efficiency by nZVI-C in partial nitritation/anammox system with a single-stage membrane-aerated biofilm reactor - Zixuan Song; Li Zhang; Jiachun Yang; Shou-Qing Ni; Yongzhen Peng (Journal of Hazardous Materials, 2024)

Amorphous/Graphitic carbon phase engineering of Corrosion-Resistant Fe@C Core-Shell nanowires for optimized dipole polarization and enhanced microwave absorption - Ping-an Yang; Wenjiao Deng; Haibo Ruan; Zhengwei Qu; Rui Li; Lirui Wang; Jiufei Luo; Zhihao Zhou; Mengjie Shou; Xin Huang; Qiao Chen; Xinglong Gong (Chemical Engineering Journal, 2024)

Significance of a minor pilin PilV in biofilm cohesion of Geobacter sulfurreducens - Xiaochun Chen; Guiqin Yang; Xiaoyun Quan; Siyue Zhu; Baoli Qin; Danyang Shou; Li Zhuang (Science of The Total Environment, 2024)

Response of anammox consortia to inhibition from high ferroferric oxide nanoparticles concentration and potential recovery mechanism - Li Zhang; Lixia Yang; Tingjun Dong; Jiachun Yang; Quanhao Dou; Shou-Qing Ni; Yongzhen Peng (Bioresource Technology, 2024)

Efficient photocatalytic reduction of nitrate byproducts during anammox process by novel extracellular polymeric substances-embedded NH2-MIL-101(Fe) photocatalysts - Li Zhang; Running Fan; Tingjun Dong; Quanhao Dou; Yongzhen Peng; Shou-Qing Ni; Jiachun Yang (Bioresource Technology, 2024)

Identification and quantitative analysis of bioactive components from Potentilla kleiniana Wight et Arn with anti HIV-1 proteases activity - Yong Qiang Zhou; Su Mei Li; Xin Wei; Xin Yang; Jun Wei Xiao; Bo Wen Pan; Shou Xia Xie; Ying Zhou; Jian Yang; Ying Wei (Natural Product Research, 2023)

The effects of Spinosad on zebrafish larvae and THP-1 cells: Associated with immune cell damage and NF-kappa B signaling pathway activation - Wei-Guo Wang; Shou-Qian Xiong; Jin Lu; Lian-Hua Zhu; Cheng Zhang; Jia-Gao Cheng; Zhong Li; Wen-Ping Xu; Li-Ming Tao; Yang Zhang (Chemosphere, 2023)

Establishment of a tilapia lake virus (TiLV)-susceptible cell line for anti-TiLV Chinese herbal compound screening - Song Zhu; Bo Miao; Yu-Zhou Zhang; Qin Yang; Xun-Teng Deng; Li-Hong Gao; Ji-Shu Zheng; De-Cheng Pu; De-Shou Wang; Sheng-Qi Su (Aquaculture, 2023)

Gliadin-based nanoparticles used for pickering stabilization: Current status and future perspective - Shuang-Qi Li; Xiao-Nan Huang; Shu-Heng Wei; Xin-Hao Yu; Xiao-Quan Yang; Jian-Hua Zhu; Shou-Wei Yin (Food Hydrocolloids, 2023)

Antimicrobial photodynamic therapy encapsulation technology: Frontier exploration and application prospects of novel antimicrobial technology - Xianjin Hu; Bingbing Shou; Lu Yang; Letian Li; Hai-Tao Ren; Jia-Horng Lin; Ching-Wen Lou; Ting-Ting Li (Chemical Engineering Journal, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Coordination effect enhanced visualization of latent fingerprint with Eu (TTA)3phen-SiO2 microspheres - Kang Zhang; Meng-Jiao Zhu; Yi-Wen Zhou; Xiao Liu; Feng Chen; Yu-Yang Zhou; Wan-Fei Li; Sheng Liu; Yun Jiang; Shou-Qing Liu (Analytica Chimica Acta, 2023)

Cinnamigones A–C, three highly oxidized guaiane-type sesquiterpenes with neuroprotective activity from Cinnamomum migao - Lang Zhou; Li-shou Yang; Li Wang; Hua-dan Liu; Ming Gao; Fa-ju Chen; Juan Yang; Qi-ji Li; Xiao-sheng Yang (Phytochemistry, 2023)

Composition and transcriptional activity of oil reservoir microorganisms under different gas/liquid ratios - Li-Bin Shou; Zhao-Wei Hou; Yi-Fan Liu; Ying Wang; Lei Zhou; Jin-Feng Liu; Shi-Zhong Yang; Ji-Dong Gu; Xiao-Lin Wu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2023)

Valorization of thermally hydrolyzed sludge with clay for sintering of ceramic tiles - Lei Wen; Lin Lin; Yi-ang Fan; Yang Luo; Sheng-shou Ma; Ying Zhou; Chao Yang; Kaimin Shih; Xiao-yan Li (Science of The Total Environment, 2023)

Comparative study of encapsulated cannabidiol ternary solid dispersions prepared by different techniques: The application of a novel technique jet milling - Hang Li; Tian-Xiao Yang; Qing-Sheng Zhao; Shou-Bu Hou; Rong-Rong Tian; Bing Zhao (Food Research International, 2023)

A Study of Combined Genotype Effects of SHCBP1 on Wool Quality Traits in Chinese Merino - Guang-Wei Ma; Shou-Zhi Wang; Ning Wang; Hui Li; Hua Yang (Biochemical Genetics, 2023)

A new phragmalin-type limonoid from the roots of Trichilia sinensis - Shou-Bai Liu; Jin-Ling Yang; Hui-Qin Chen; Cheng-min Yang; Hao Wang; Cai-Hong Cai; Jing-Zhe Yuan; Wen-Li Mei; Hao-Fu Dai (Phytochemistry Letters, 2023)

Potential millennial‐scale avian declines by humans in southern China - Feng Dong; Qiang Zhang; Yi‐Lin Chen; Fu‐Min Lei; Shou‐Hsien Li; Fei Wu; Xiao‐Jun Yang (Global Change Biology, 2022)
Mounting observational records demonstrate human‐caused faunal decline in recent decades, while accumulating archaeological evidence suggests an early biodiversity impact of human activities during the Holocene. A fundamental question arises concerning whether modern wildlife population declines began during early human disturbance. Here, we performed a population genomic analysis of six common forest birds in East Asia to address this question. For five of them, demographic history inference based on 25–33 genomes of each species revealed dramatic population declines by 4‐ to 48‐fold over millennia (e.g. 2000–5000 thousand years ago). Nevertheless, summary statistics detected nonsignificant correlations between these population size trajectories and Holocene temperature variations, and ecological niche models explicitly predicted extensive range persistence during the Holocene, implying limited demographic consequence of Holocene climate change. Further analyses suggest high negative correlations between the reconstructed population declines and human disturbance intensities and indicate a potential driver of human activities. These findings provide a deep‐time and large‐scale insight into the recently recognized avifaunal decline and support an early origin hypothesis of human effects on biodiversity. Overall, our study sheds light on the current biodiversity crisis in the context of long‐term human–environment interactions and offers a multi‐evidential framework for quantitatively assessing the ecological consequences of human disturbance.

The role of demographic compensation in stabilising marginal tree populations in North America - Xianyu Yang; Amy L. Angert; Pieter A. Zuidema; Fangliang He; Shongming Huang; Shouzhong Li; Shou‐Li Li; Nathalie I. Chardon; Jian Zhang (Ecology Letters, 2022)
Demographic compensation—the opposing responses of vital rates along environmental gradients—potentially delays anticipated species’ range contraction under climate change, but no consensus exists on its actual contribution. We calculated population growth rate (λ) and demographic compensation across the distributional ranges of 81 North American tree species and examined their responses to simulated warming and tree competition. We found that 43% of species showed stable population size at both northern and southern edges. Demographic compensation was detected in 25 species, yet 15 of them still showed a potential retraction from southern edges, indicating that compensation alone cannot maintain range stability. Simulated climatic warming caused larger decreases in λ for most species and weakened the effectiveness of demographic compensation in stabilising ranges. These findings suggest that climate stress may surpass the limited capacity of demographic compensation and pose a threat to the viability of North American tree populations.

Not out of the woods yet: Signatures of the prolonged negative genetic consequences of a population bottleneck in a rapidly re‐expanding wader, the black‐faced spoonbill Platalea minor - Shou‐Hsien Li; Yang Liu; Chia‐Fen Yeh; Yuchen Fu; Carol K. L. Yeung; Chun‐Cheng Lee; Chi‐Cheng Chiu; Tung Hui Kuo; Fang‐Tse Chan; Yu‐Chia Chen; Wen‐Ya Ko; Cheng‐Te Yao (Molecular Ecology, 2022)
The long‐term persistence of a population which has suffered a bottleneck partly depends on how historical demographic dynamics impacted its genetic diversity and the accumulation of deleterious mutations. Here we provide genomic evidence for the genetic effect of a recent population bottleneck in the endangered black‐faced spoonbill ( Platalea minor ) after its rapid population recovery. Our data suggest that the bird's effective population size, N e , had been relatively stable (7500–9000) since 22,000 years ago; however, a recent brief yet severe bottleneck ( N e = 20) which we here estimated to occur around the 1940s wiped out >99% of its historical N e in roughly three generations. Despite a >15‐fold population recovery since 1988, we found that black‐faced spoonbill population has higher levels of inbreeding (7.4 times more runs of homozygosity) than its sister species, the royal spoonbill ( P. regia ), which is not thought to have undergone a marked population contraction. Although the two spoonbills have similar levels of genome‐wide genetic diversity, our results suggest that selection on more genes was relaxed in the black‐faced spoonbill; moreover individual black‐faced spoonbills carry more putatively deleterious mutations (Grantham's score > 50), and may therefore express more deleterious phenotypic effects than royal spoonbills. Here we demonstrate the value of using genomic indices to monitor levels of genetic erosion, inbreeding and mutation load in species with conservation concerns. To mitigate the prolonged negative genetic effect of a population bottleneck, we recommend that all possible measures should be employed to maintain population growth of a threatened species.

Potential Himalayan community turnover through the Late Pleistocene - Feng Dong; Chih-Ming Hung; Shou-Hsien Li; Xiao-Jun Yang (Climatic Change, 2021)

Structure and Functional Diversity of Surface Bacterioplankton Communities in an Overwintering Habitat for Large Yellow Croaker, Pseudosciaena crocea, of the Southern East China Sea - Wen Yang; Shi-Zhan Zheng; Shou-Heng Zhou; Li Zhao; Jin-Yong Zhu; Betina Lukwambe; Regan Nicholaus; Cheng-Hua Li; Zhong-Ming Zheng (Frontiers in Marine Science, 2020)

Source Identification of Trace Elements in Peri-urban Soils in Eastern China - Long Sun; Manus Carey; Lei Yang; Li-Ding Chen; Shou-Juan Li; Fang-Kai Zhao; Yong-Guan Zhu; Caroline Meharg; Andrew A. Meharg (Exposure and Health, 2019)

Diversification of mitogenomes in three sympatric Altica flea beetles (Insecta, Chrysomelidae) - Rui‐E Nie; Jing Wei; Shou‐Ke Zhang; Alfried P. Vogler; Ling Wu; Alexander S. Konstantinov; Wen‐Zhu Li; Xing‐Ke Yang; Huai‐Jun Xue (Zoologica Scripta, 2019)
The Asian flea beetles Altica cirsicola , Altica fragariae and Altica viridicyanea are broadly sympatric and morphologically highly similar but feed on distantly related host plants. They have been suggested as a model for ecological speciation studies. However, their phylogeny and species limits remain uncertain. In this study, we added mitochondrial genomes from multiple individuals of each species to the growing database. Phylogenetic analyses based on 15 genes showed clear interspecific divergences of A. fragariae from the other species, but A. cirsicola and A. viridicyanea were not distinguishable by distance‐based or tree‐based methods of species delimitation due to non‐monophyly of mitogenomes relative to the morphologically defined entities, possibly affected by interspecific introgression. This was confirmed by wider sampling of mitochondrial COX1 (58 individuals) and the second internal transcribed spacer of nuclear ribosomal RNA cluster (ITS2; 68 individuals), which showed that ITS2, but not COX1, coincided with the morphological species limits. The full mitochondrial genomes are not able to shed further light on the species status, even with the most sensitive approach based on diagnostic characters, yet the whole mitogenome is useful to get improved estimates of intra‐ and interspecific variation, not affected by the stochastic error seen in individual genes.

Geochemistry, zircon U–Pb geochronology and Hf isotopes of Jurassic-Cretaceous granites in the Tengchong terrane, SW China: implications for the Mesozoic tectono-magmatic evolution of the Eastern Tethyan Tectonic Domain - Hua-Wen Cao; Yun-Hui Zhang; Li Tang; Steven P. Hollis; Shou-Ting Zhang; Qiu-Ming Pei; Chang Yang; Xiao-Shuan Zhu (International Geology Review, 2019)

Ethanol Alters APP Processing and Aggravates Alzheimer-Associated Phenotypes - Daochao Huang; Mengjiao Yu; Shou Yang; Dandan Lou; Weitao Zhou; Lingling Zheng; Zhe Wang; Fang Cai; Weihui Zhou; Tingyu Li; Weihong Song (Molecular Neurobiology, 2018)

Transcriptome analysis provides insights into wood formation during larch tree aging - Wan-Feng Li; Wen-Hua Yang; Shou-Gong Zhang; Su-Ying Han; Li-Wang Qi (Tree Genetics & Genomes, 2017)

Inhibitory effect of Shenqi Fuzheng injection combined with docetaxel on lung cancer cells - Bo-yu Dong; Cheng Wang; Li Tan; Ning Tan; Meng-di Zhao; Yang Lu; Shou-ying Du (Journal of Zhejiang University-SCIENCE B, 2017)

Sino‐Himalayan mountains act as cradles of diversity and immigration centres in the diversification of parrotbills (Paradoxornithidae) - Yang Liu; Junhua Hu; Shou‐Hsien Li; Pablo Duchen; Daniel Wegmann; Manuel Schweizer (Journal of Biogeography, 2016)
Aim Montane regions like the Sino‐Himalayas constitute global diversity hotspots. Various mechanisms such as in situ adaptive divergence, speciation following immigration or allopatric diversification in complex landscapes have been proposed to account for the exceptional diversity found in a particular clade in a montane setting. We investigated macroevolutionary patterns to test these different hypotheses in the continental radiation of a Sino‐Himalayan bird group, the parrotbills (Paradoxornithidae). Location Sino‐Himalayan region, Indo‐Burma. Methods We used phylogenetic comparative methods based on a multilocus, time‐calibrated phylogeny to reconstruct patterns of lineage diversification, biogeographical history, morphological evolution as well as of climate niche history using ecological niche modelling. Results The radiation of parrotbills started c. 12 Ma, diversifying at an apparent constant rate over time. The biogeographical history appears to be complex, within‐region speciation in mountains was restricted to China. Size evolution was concentrated in the early phase of parrotbill radiation, whereas morphological shape evolution did not differ from Brownian motion. We found no indication for niche conservatism, with climate niche evolution occurring throughout the radiation of parrotbills. Conclusions Parrotbills diversified within a time span of increased regional orogenesis and associated strong climate change. While the south‐west and central Chinese mountains were revealed to be a species pump, with in situ allopatric diversification triggered by complex topography and high habitat turnover, the diversity in the Himalayas was chiefly the result of immigration. Evidence for continuous ecological specialization and for the absence of climate niche conservatism could be interpreted as the consequence of ongoing climate‐ and habitat‐induced ecological opportunities. The radiation of parrotbills demonstrates the influence of multiple drivers of diversification in a single group due to the dynamic geological and palaeoclimatic history of the Sino‐Himalayan region and illustrates the complex nature of continental radiations.

Experimental and numerical study on fracture propagation near open-hole horizontal well under hydraulic pressure - Shou Ma; Jianchun Guo; Lianchong Li; Yingjie Xia; Tao Yang (European Journal of Environmental and Civil Engineering, 2016)

Marker-assisted breeding for transgressive seed protein content in soybean [Glycine max (L.) Merr.] - Ying Hu Zhang; Mei Feng Liu; Jian Bo He; Yu Feng Wang; Guang Nan Xing; Yan Li; Shou Ping Yang; Tuan Jie Zhao; Jun Yi Gai (Theoretical and Applied Genetics, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Testing hypotheses of mitochondrial gene‐tree paraphyly: unravelling mitochondrial capture of the Streak‐breasted Scimitar Babbler ( P omatorhinus ruficollis ) by the Taiwan Scimitar Babbler ( P omatorhinus musicus ) - Feng Dong; Fa‐Sheng Zou; Fu‐Min Lei; Wei Liang; Shou‐Hsien Li; Xiao‐Jun Yang (Molecular Ecology, 2014)
Species‐level paraphyly inferred from mitochondrial gene trees is a prevalent phenomenon in taxonomy and systematics, but there are several potential causes that are not easily explained by currently used methods. This study aimed to test the underlying causes behind the observed paraphyly of Streak‐breasted Scimitar Babbler ( P omatorhinus ruficollis ) via statistical analyses of four mitochondrial (mt DNA ) and nine nuclear (nu DNA ) genes. Mitochondrial gene trees show paraphyly of P . ruficollis with respect to the Taiwan Scimitar Babbler ( P omatorhinus musicus ), but nuclear genealogies support a sister‐group relationship. Predictive coalescent simulations imply several hypothetical explanations, the most likely being mitochondrial capture of P . ruficollis by P . musicus for the observed cyto‐nuclear incongruence. Further approximate Bayesian computation suggests a unidirectional introgression model with substantial level of gene flow from P . ruficollis to P . musicus during their initial divergence during the Late Pleistocene. This specific observation frames several potential causes for incongruent outcomes of mitochondrial and nuclear introgression in general, and on the whole, our results underscore the strength of multiple independent loci for species delimitation and importance of testing hypotheses that explain disparate causes of mitochondrial gene‐tree paraphyly.

Species delimitation in the C hinese bamboo partridge B ambusicola thoracica ( P hasianidae; A ves) - Chih‐Ming Hung; Hsin‐Yi Hung; Chia‐Fen Yeh; Yi‐Qiang Fu; De Chen; Fumin Lei; Cheng‐Te Yao; Chiou‐Ju Yao; Xiao‐Jun Yang; Yu‐Ting Lai; Shou‐Hsien Li (Zoologica Scripta, 2014)
Although tropical and subtropical Asia harbour a high level of species diversity, their species richness can be underestimated because species which are in fact distinct have not been separately identified. In this study, we delimit B ambusicola thoracica into two full species, the Chinese bamboo partridge ( B. thoracica ) in continental Asia and the Taiwanese bamboo partridge ( B . sonorivox ) on the island of Taiwan, using coalescent‐based multilocus division and diagnosable vocalization patterns. Isolation‐with‐migration analysis indicated that the two bamboo partridges diverged approximately 1.8 million years ago, with gene flow present most probably during the early stages of their divergence. This conclusion supports the hypothesis that diverging lowland lineages spread across the Asian mainland, and continental islands have more opportunities for secondary contact than highland ones when the sea level was low. Our results imply that conservation of biodiversity in tropical and subtropical Asia could be hindered by overlooking numerous ‘hidden’ species and highlight the importance of re‐examining the taxonomic statuses of species in this region traditionally defined as polytypic.

Establishment and characterization of dairy cow growth hormone secreting anterior pituitary cell model - Jian-Fa Wang; Shou-Peng Fu; Su-Nan Li; Zhan-Qing Yang; Wen-Jing Xue; Zhi-Qiang Li; Wei Wang; Ju-Xiong Liu (In Vitro Cellular & Developmental Biology - Animal, 2014)

Comparative pharmacokinetics of borneol in cerebral ischemia-reperfusion and sham-operated rats - Pan Xu; Ying Li; Shou-Ying Du; Yang Lu; Jie Bai; Qing-li Guo (Journal of Zhejiang University-SCIENCE B, 2014)

Cytochrome P450 2A13 is an efficient enzyme in metabolic activation of aflatoxin G1 in human bronchial epithelial cells - Zhan Zhang; Xuejiao Yang; Yun Wang; Xichen Wang; Huiyuan Lu; Xiaoming Zhang; Xue Xiao; Shushu Li; Xinru Wang; Shou-Lin Wang (Archives of Toxicology, 2013)

Glacial expansion and diversification of an East Asian montane bird, the green‐backed tit ( Parus monticolus ) - Wenjuan Wang; Bailey D. McKay; Chuanyin Dai; Na Zhao; Ruiying Zhang; Yanhua Qu; Gang Song; Shou‐Hsien Li; Wei Liang; Xiaojun Yang; Eric Pasquet; Fumin Lei (Journal of Biogeography, 2013)
Aim We combined genetic sequence data and ecological niche modelling to resolve the impacts of past climatic fluctuations on the distribution, genetic diversification, and demographic dynamics of an East Asian montane bird, the green‐backed tit ( Parus monticolus ). Location East Asia. Methods Phylogenetic analyses were carried out using four mitochondrial fragments and seven nuclear loci from 161 birds sampled from 29 localities spanning the entire geographical range of the green‐backed tit. We used * beast to estimate the species tree and calculate divergence times. Extended Bayesian skyline plots were used to infer potential historical shifts in population size. We used MaxEnt to predict potential distributions during three periods: the present day, the Last Glacial Maximum and the Last Interglacial. Results The mitochondrial DNA (mt DNA ) gene tree showed strong support for three reciprocally monophyletic groups: a south‐western clade, a central clade and a Taiwanese clade. Taiwanese and Vietnamese samples had fixed differences at several nuclear loci, but the south‐western and central samples shared haplotypes at all nuclear loci. The mt DNA gene tree topology differed from the species tree topology. The species tree suggested sister relationships between Taiwanese and Vietnamese operational taxonomic units ( OTU s) and between south‐western and central OTU s. Diversification within the green‐backed tit was relatively recent, probably within the last 0.9 million years. Extended Bayesian skyline plots suggested rapid population expansion in the south‐western and central phylogroups after the Last Interglacial, and this result was consistent with ecological niche models. Main conclusions Our results suggest that genetic diversification within the green‐backed tit was affected by the later Pleistocene climate fluctuations. Ecological niche models indicated that the present‐day vegetation distribution was, in many ways, more similar to that of the Last Glacial Maximum than it was to that of the Last Interglacial. Continental populations of the green‐backed tit experienced unusual demographic and range expansion that is likely to have occurred during the cooling transition between the Last Interglacial and the Last Glacial Maximum. We found incongruence between the mt DNA gene tree and the species tree, which underscores the importance of using both mitochondrial and nuclear markers when estimating the evolutionary history of populations.

Molecular epidemiology of hepatitis C virus among different groups of people in the province of Fujian, China - Ying Ye; Yan-sheng Yan; Ge Chen; Ping-ping Yan; Wu-xiong Zheng; Yan-qin Deng; Xiu-hui Yang; Shou-li Wu; Zhi-shan Zhang (Archives of Virology, 2013)

HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Involvement of FGF9/16/20 subfamily in female germ cell development of the Nile tilapia, Oreochromis niloticus - Yun-Lv Sun; Sheng Zeng; Kai Ye; Chao Yang; Ming-Hui Li; Bao-Feng Huang; Li-Na Sun; Lin-Yan Zhou; De-Shou Wang (Fish Physiology and Biochemistry, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Influence of sintering temperature on the characteristics of shale brick containing oil well-derived drilling waste - Xiang-Guo Li; Yang Lv; Bao-Guo Ma; Shou-Wei Jian; Hong-Bo Tan (Environmental Science and Pollution Research, 2011)

Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves) - Hsu‐Chun Wu; Rong‐Chien Lin; Hsin‐Yi Hung; Chia‐Fen Yeh; Jui‐Hua Chu; Xiao‐Jun Yang; Chiou‐Ju Yao; Fa‐Sheng Zou; Cheng‐Te Yao; Shou‐Hsien Li; Fu‐Min Lei (Zoologica Scripta, 2011)
Wu, H.‐C., Lin, R.‐C., Hung, H.‐Y., Yeh, C.‐F., Chu, J.‐H., Yang, X.‐J., Yao, C.‐J., Zou, F.‐S., Yao, C.‐T., Li, S.‐H. & Lei, F.‐M. (2011). Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves). — Zoologica Scripta, 40 , 468–478. The Vinaceous Rosefinch ( Carpodacus vinaceus ) is endemic in East Asia with two recognized subspecies – C. v. vinaceus , distributed along the eastern edge of the Tibetan Plateau and the Himalayas, and C. v. formosanus , restricted to Taiwan’s Central Mountain Range. As reflected in a controversial taxonomic history, this vastly disjunctive distribution pattern suggests that the subspecies, having been isolated from each other for a long time, might have diverged, challenging the current taxonomic treatment and calling for possible species delimitation. Sequences of two mitochondrial fragments (mtDNA) and two Z‐linked nuclear loci (zDNA) were used to reconstruct the intraspecific phylogeny of C. vinaceous . The mtDNA tree shows that the two subspecies of the vinaceous rosefinch form two exclusively monophyletic clades. All but one zDNA sequences from the nominate subspecies and C. v. formosanus also formed exclusively monophyletic clades (the exceptional zDNA sequence from C. v. vinaceous formed a weakly supported clade with two outgroup species). Moreover, by conducting quantitative comparisons of morphometric traits and male plumage coloration, we found that the two subspecies exhibit distinguishable morphological differences. All the evidence therefore suggests that C. v. formosanus is a cryptic species and that its taxonomic status should be restored to full species. Molecular dating suggests that the two sibling rosefinches split 1.7 ± 0.2 million years ago, providing a point estimate for the historical connectivity of biota between eastern Tibet‐Himalayas and montane Taiwan.

Abnormal expression of NRF-2α in hepatocellular carcinoma identified with a newly prepared monoclonal antibody against human NRF-2α protein - Ya Qing Zhang; Kai Nan Li; Ji Hong Cui; Yan Fang Liu; Shou Jing Yang (Molecular Biology Reports, 2011)

Norovirus Gastroenteritis Outbreak is Associated with Contaminated Drinking Water in South China - Ya-Qing He; Han-Wu Ma; Xiang-Jie Yao; Qing-Lan Bu; Hong Yang; Wei Huang; Yong-Xiang Duan; Hai-Long Zhang; Chuan-Wen Dai; Wei-Ke Li; Shou-Yi Yu (Food and Environmental Virology, 2010)

Cytogenetic analysis of reciprocal hybrids and their parents between Larix leptolepis and Larix gmelinii: implications for identifying hybrids - Shou Gong Zhang; Wen Hua Yang; Su Ying Han; Bo Tao Han; Mao Xue Li; Li Wang Qi (Tree Genetics & Genomes, 2010)

Ischemic compression block attenuates mechanical hyperalgesia evoked from latent myofascial trigger points - Yong-Hui Wang; Xin-Li Ding; Yang Zhang; Jing Chen; Hong-You Ge; Lars Arendt-Nielsen; Shou-Wei Yue (Experimental Brain Research, 2010)

Frequent occurrence of unreduced gametes in Triticum turgidum–Aegilops tauschii hybrids - Lian-Quan Zhang; Deng-Cai Liu; You-Liang Zheng; Ze-Hong Yan; Shou-Fen Dai; Yun-Fang Li; Qi Jiang; Ya-Qing Ye; Yang Yen (Euphytica, 2010)

Changes in H2O2 content and antioxidant enzyme gene expression during the somatic embryogenesis of Larix leptolepis - Shou-gong Zhang; Su-ying Han; Wen-hua Yang; Hua-li Wei; Ming Zhang; Li-wang Qi (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Estimating Long-Term Changes in China’s Village Landscapes - Erle Christopher Ellis; Nagaraj Neerchal; Kui Peng; Hong Sheng Xiao; Hongqing Wang; Yan Zhuang; Shou Cheng Li; Jun Xi Wu; Jia Guo Jiao; Hua Ouyang; Xu Cheng; Lin Zhang Yang (Ecosystems, 2009)

Development of male gametophyte of Larix leptolepis Gord. with emphasis on diffuse stage of meiosis - Shou-Gong Zhang; Wen-Hua Yang; Yu-Chen Qi; Mao-Xue Li; Jian-Hua Wang; Xiao-Mei Sun; Xiao-Shan Wang; Li-Wang Qi (Plant Cell Reports, 2008)

Effect of SPLUNC1 protein on the Pseudomonas aeruginosa and Epstein-Barr virus - Hou-De Zhou; Xiao-Ling Li; Gui-Yuan Li; Ming Zhou; Hua-Ying Liu; Yi-Xing Yang; Tan Deng; Jian Ma; Shou-Rong Sheng (Molecular and Cellular Biochemistry, 2008)

Tissue distribution of the secretory protein, SPLUNC1, in the human fetus - Hou-De Zhou; Song-Qin Fan; Jin Zhao; Dong-Hai Huang; Ming Zhou; Hua-Ying Liu; Zhao-Yang Zeng; Yi-Xing Yang; He Huang; Xiao-Ling Li; Shou-Rong Shen; Gui-Yuan Li (Histochemistry and Cell Biology, 2006)

Influence of polarized bias and porous silicon morphology on the electrical behavior of Au-porous silicon contacts - Yue Zhao; Dong-sheng Li; Shou-xiang Xing; De-ren Yang; Min-hua Jiang (Journal of Zhejiang University-SCIENCE B, 2005)